Leptin levels in different forms of Chagas' disease - Fernandes,F. (2007)
Leptin is produced primarily by adipocytes. Although originally associated with the central regulation of satiety and energy metabolism, increasing evidence indicates that leptin may be an important mediator in cardiovascular pathophysiology. The aim of the present study was to investigate plasma leptin levels in patient with Chagas' heart disease and their relation to different forms of the disease. We studied 52 chagasic patients and 30 controls matched for age and body mass index. All subjects underwent anthropometric, leptin and N-terminal pro-brain natriuretic peptide (NT-proBNP) measurements and were evaluated by echocardiography, 12-lead electrocardiogram (ECG), and chest X-ray. All patients had fasting blood samples taken between 8:00 and 9:00 am. Chagasic patients were divided into 3 groups: group I (indeterminate form, IF group) consisted of 24 subjects with 2 positive serologic reactions for Chagas' disease and no cardiac involvement as evaluated by chest X-rays, ECG and two-dimensional echocardiography; group II (showing ECG abnormalities and normal left ventricular systolic function, ECG group) consisted of 14 patients; group III consisted of 14 patients with congestive heart failure (CHF group) and left ventricular dysfunction. Serum leptin levels were significantly lower (P < 0.001) in the CHF group (1.4 ± 0.8 ng/mL) when compared to the IF group (5.3 ± 5.3 ng/mL), ECG group (9.7 ± 10.7 ng/mL), and control group (8.1 ± 7.8 ng/mL). NT-proBNP levels were significantly higher (P < 0.001) in the CHF group (831.8 ± 800.1 pg/mL) when compared to the IF group (53.2 ± 33.3 pg/mL), ECG group (83.3 ± 57.4 pg/mL), and control group (32 ± 22.7 pg/mL). Patients with Chagas' disease and an advanced stage of CHF have high levels of NT-ProBNP andlow plasma levels of leptin. One or more leptin-suppressing mechanisms may operate in chagasic patients.